Graphic design and 21st century bookworks: implementing multimodal strategies to include e-pub and interactive pdf formats to complement traditional book formats - Kaiser, L; Cochrane, T; Spooner, H; Karmokar, S; Austin, L; Garden, E; Potter, E; Young, A; Wilczynska, K (Higher Education Research and Development Society of Australasia (HERDSA), 2013)
The overall goal of this project was to introduce multimodal approaches to meet the need for increased digital literacy and to integrate new technology into tertiary graphic design courses at AUT University. Traditionally these courses have involved designing, creating, and crafting books for print, and binding books by hand. This project explores how old and new technologies might be utilised in design studios and in the bindery for the creation of multimodal books that combine the best aspects of printed limited edition and hand-made books with the enhanced communication and reading potential of e-publication. Graphic Design is a discipline that is undergoing major changes in its associated technologies; while underlying design principles may remain fundamentally intact, new digital technologies and publishing mediums provide new challenges and opportunities, and require new approaches. The intention of the project is to engage staff in a Graphic Design Community of Practice (GD CoP) to collectively engage in developing digital literacy and new mobile technologies in tertiary Graphics teaching. Members were given access to iPads for teaching purposes and to extend their knowledge of the digital publishing environment. The two main project areas were: 1) Issues, Theory and Formats: 21st Century Bookworks (1st year BDes Graphics): Digital technologies were introduced into traditional workspaces such as the book bindery and students combined old and new technologies to create multimodal books. 2) Integrating digital technology into productivity and workflow in The Studio (Post Graduate Diploma). Outcomes and documentation of these research initiatives at http://gdcop.wordpress.com and http:/lesleykaiser.wordpress.com